Beta Binaural Beats and its effects on the Cognition of Nursing Students in a Private Higher Education Institution - Julie Ann C. Dy; April Ross S. Ladera; Joshua Paul J. Cabato; Monique O. Librando; Johnny Jr J Yao (Faculty of Nursing Universitas Padjadjaran, 2020)
Studying nursing comes with a certain expectation to work hard and take a certain amount of time. A promising method called beta binaural beats is thought to improve cognitive functions. This study aimed to determine whether listening to beta beats is an effective method for improving cognition among nursing students. A double-blinded experimental research design was utilized and measured the effects of the intervention towards memory, abstract reasoning and reading comprehension. A total of 89 subjects participated in this study. Only the score of reading comprehension showed a significant difference (t=2.38, p=.02). The findings suggest that beta beats is an effective way in enhancing reading comprehension. However, findings show that beats aren’t effective in enhancing memory and abstract reasoning. Therefore, this may be used as a method to enhance learning.